Structure and luminescence variations in Cd(II) mixed-ligands coordination compounds influenced by coordination modes of naphthalene-1, 5-disulfonate and configuration of flexible bis(pyridyl) ligands. (18th April 2017) - Han, Jing; Huo, Li-Hua; Deng, Zhao-Peng; Gao, Shan
Graphical abstract: Five Cd(II) mixed-ligands compounds with diverse mononuclear, "8" shaped chain, 4 4 and 3 6 layers, as well aspcu net have been synthesized, which exhibit strong violet and blue emissions in the solid state. Abstract: Hydrothermal reaction of Cd(OAc)2, naphthalene-1, 5-disulfonic acid (1, 5-H2 NDS) and different flexible bis(pyridyl) ligands in water or mixed ethanol–water solution gives rise to the formation of five new Cd(II) coordination compounds, [Cd(L1)2 (H2 O)2 ] n ·n(1, 5-NDS) (1 ), [Cd(1, 5-NDS)(L2)2 ] n (2 ), [Cd(HL3)2 (H2 O)4 ] n ·2n(1, 5-NDS)·2nH2 O (3 ), [Cd(1, 5-NDS)(L4)2 ] n (4 ) and [Cd(1, 5-NDS)(L5)2 ] n (5 ) [L1 = N -(pyridin-4-ylmethyl)pyridin-3-amine, L2 = N -(pyridin-3-ylmethyl)pyridin-3-amine, L3 = N -(pyridin-3-ylmethyl) pyridin-2-amine, L4 = N, N ′-(1, 4-phenylenebis(methylene))bis(pyridin-3-amine), L5 = N, N ′-(1, 3-phenylenebis (methylene))bis(pyridin-3-amine)], which have been characterized by elemental analysis, infrared (IR) spectroscopy, thermogravimetric (TG) analysis, photoluminescence (PL) spectroscopy, powder and single-crystal X-ray diffraction. In compounds1 and2, the short bis(pyridyl) ligands L1 and L2 join adjacent Cd(II) cations into "8" shaped chains while the short protonated L3 ligand in compound3 only coordinates to Cd(II) cation in terminal mode. In contrast, the long bis(pyridyl) ligands L4 and L5 in compounds4 and5 connect adjacent Cd(II) cations into 4 4 layer motifs. The 1, 5-NDS 2− acts as counter-anions in compounds1, 3 and bridging anions in compounds2, 4 and5, giving rise to diverse supramolecular network (1 and3 ), 4 4 (2 ) and 3 6 (4 ) layers, as well aspcu net (5 ). Moreover, solid-state luminescent properties demonstrate that compounds1 –5 exhibit strong emissions varying from 387 to 468 nm.